Ecogeographical gradients in plumage coloration among Australasian songbird clades. Issue 3 (25th September 2016) - Friedman, Nicholas R.; Remeš, Vladimír
Abstract: Aim: Animal coloration often shows high degrees of evolutionary lability, producing variation among species that is easily apparent. This variation may produce consistent geographical patterns as species converge on adaptive phenotypes in similar environments. Some such geographical patterns in colour variation have been recently predicted as a response to the light environment in different habitats. Others like Gloger's rule – the negative relationship between brightness and humidity – have long been observed but still demand explanation. Finally, the conventional wisdom that tropical birds are more colourful remains largely untested. Location: Australia, New Guinea. Methods: Here, we compared plumage coloration across two families of Australian birds (Meliphagidae, n = 97 species; Acanthizidae, n = 40 species) in a combined spatial and phylogenetic framework. We assessed the extent to which environmental variables extracted from species ranges explain variation in colour traits, while correcting for the autocorrelation inherent in spatially structured data using extensive simulations. Results: We found several strong effects of environment on plumage coloration. Inland species with ranges marked by high aridity and temperature seasonality showed greater colour span among acanthizids, and greater saturation among meliphagids. Gloger's rule was supported in both clades, but more strongly for dorsal plumage. The most consistent correlate in this relationship was vegetation: birds in regions with more vegetation had markedly darker plumage. Ornament hue showed no significant associations with vegetation or climate. Main conclusions: Birds living close to the equator were not more colourful, but species inhabiting arid regions were. Species may respond to the shorter and less predictable breeding seasons of arid environments by evolving increased ornamentation. The consistent relationship we observed between vegetation and dorsal brightness supports a primary role for countershading and background matching in Gloger's rule.